FORMULASI PASTA GIGI INFUSA DAUN JAMBU BIJI (Psidium guajavaLinn.) DENGAN VARIASI KONSENTRASI Na. CMC SEBAGAI BAHAN PENGIKAT - Nur Sa'adah Daud; Sulasni Atma Desi; Mus Ifaya (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2016)
Guava leaves (Psidium guajava Linn.) has been shown inhibiting effect against dental caries causing bacteria such as Staphylococcus aureus and Streptococcus mutans. In order to facilitate its activity in overcoming dental caries,formulation into dosage toothpaste was needed. The purpose of this study was to formulate toothpaste from infuse of guava leaves with variations concentration of Sodium Carboxymethylcellulosa as a binder to obtain the best toothpaste formula. The concentration of infuse of guava leaves was 5% and 4%, 6% and 8%for Sodium carbxymethylcellulose respectively for formula each formula. Other additives have been used, they were calcium carbonate, glycerin, sodium lauryl sulfate, α-tocopherol, propyl paraben, methyl paraben, Oleum Menthae Piperatae (OMP) and distilled water.The results showed that three toothpaste formula from the organoleptic testwere white coloured, mint flavored with soft and lumpy of textur, with the mean of pH value of 6,9 to 8,3 were eligible, and the foam height value of 3,5 to 5,5 cm. Theviscosity values were increased with the increasing concentration ofSodium carbxymethylcellulose. While the preference test showedthat toothpaste formula C was the most preferred.